Revelació, apoteosi i confirmació. El retaule de la Transfiguració de la Catedral de Tortosa. - GREGORI, RUBÉN (Scripta)
This article aims to highlight the paradigmatic iconography of the altarpiece of the Transfiguration of the Cathedral of Tortosa attributed to Rafael Vergós and Pere Alemany (ca. 1498). Firstly, the meaning and imprint of the episode of the New Testament will be analyzed and it will be put in relation to the scenes chosen for the altarpiece. In the same way, it will be highlighted the possible role of the socio-religious context of the moment as an articulating axis of the visual program of the artwork.